Job Satisfaction Among Nurses in Primary Healthcare Centers: Examining the Predictive Roles of Psychosocial Factors - Joy Abu; Shyngle K. Balogun; Emmanuel E. Uye (Tinta Emas Publisher, 2026)
Nurses' job satisfaction is central to healthcare quality, retention, and service continuity, particularly in primary healthcare centers where nurses often work under limited resources. This study examined whether psychosocial factors, namely autonomy, supervision, social support, work-life balance, compensation, and marital satisfaction, jointly and independently predict job satisfaction among nurses in primary healthcare centers in Ibadan, Nigeria. A cross-sectional quantitative survey design was employed. Using multistage sampling, data were collected from 150 nurses in selected urban and rural local government areas in Ibadan through validated scales measuring job satisfaction and psychosocial factors. Zero-order correlation and multiple regression analyses were performed using IBM SPSS version 26 at a significance level of p < 0.05. The results showed that the psychosocial factors jointly predicted job satisfaction, R = 0.417, R² = 0.174, F(6, 144) = 5.036, p < 0.05. Autonomy (β = 0.303, p < 0.05), social support (β = -0.472, p < 0.05), and compensation (β = 0.495, p < 0.05) independently predicted job satisfaction, whereas supervision (β = 0.130, p > 0.05), work-life balance (β = 0.102, p > 0.05), and marital satisfaction (β = -0.272, p > 0.05) were not significant independent predictors. The findings indicate that institutional policies that strengthen nurses' autonomy, social support systems, and compensation structures may improve job satisfaction in primary healthcare settings.